2013
DOI: 10.1038/ajg.2013.287
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Is More Effective Than Azathioprine and Mesalamine at Preventing Postoperative Recurrence of Crohn's Disease: A Randomized Controlled Trial

Abstract: The administration of ADA after intestinal resective surgery was greatly effective in preventing endoscopic and clinical recurrence of CD. Further larger studies are necessary to confirm the therapeutic advantage and to show the economic implications of biologic therapy in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
80
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(88 citation statements)
references
References 43 publications
4
80
2
Order By: Relevance
“…Infliximab therapy significantly improved endoscopic inflammation and reduced the risk of subsequent clinical recurrence. In contrast, recent randomized controlled trials (RCTs) found that anti-TNF therapy with infliximab or adalimumab initiated soon after surgery was useful in preventing postoperative recurrence in CD [9][10][11]. Should we start anti-TNF therapy soon after surgery or after confirming early endoscopic recurrence?…”
mentioning
confidence: 75%
“…Infliximab therapy significantly improved endoscopic inflammation and reduced the risk of subsequent clinical recurrence. In contrast, recent randomized controlled trials (RCTs) found that anti-TNF therapy with infliximab or adalimumab initiated soon after surgery was useful in preventing postoperative recurrence in CD [9][10][11]. Should we start anti-TNF therapy soon after surgery or after confirming early endoscopic recurrence?…”
mentioning
confidence: 75%
“…In another prospective trial from Italy, Saverino et al 23 compared the role of ADA with that of azathioprine and mesalamine after resection. The authors concluded that the PER rates after ileocolic resection in the 18 patients treated with ADA (6.3%) were significantly lower than those in the 17 patients treated with azathioprine (64.7%) and in the 16 patients treated with mesalamine (83.3%) after 2 years of follow-up (P=0.0017) (Fig.…”
Section: Adalimumab In the Prevention Of Postoperative Endoscopic Recmentioning
confidence: 99%
“…24 There are not yet comparative effectiveness data for thiopurines and TNF antagonists for the indication of prevention of post-operative recurrence, but early data suggest a very large effect size for TNF antagonists. 25,26 If TNF antagonists had a similar low cost as generic thiopurines, there would likely be little debate regarding an evolution towards treatment of CD with TNF antagonists, either as monotherapy or ideally as combination therapy. Unfortunately, this is not the world that we live in.…”
mentioning
confidence: 99%